Concrete with Bottom Ash as a Replacement for Fine Aggregate Fails Mechanical Tests at Coal Washeries (International Journal of Innovative Research in Computer Science & Technology, 2023)
Critical research is focused on the use of  a variety of commercial waste products as alternatives to  total, such as coal pyrophoric waste, heater slag,  fibreglass waste products, elastic waste plastics, work  slime pellets, and so on. If waste materials are employed  in place of bond mortar and cement in their entirety, the  utilisation of waste materials will become more  complex. This method of waste material utilisation can  address issues with total shortage in various  development locations as well as environmental  concerns related to total mining and trash transit.  Because the totals will effectively manage the  characteristics of cement, their characteristics have a  phenomenally spectacular significanceSo, before using  any waste material as a total in cement, a radical analysis  is essential followed by a thorough appraisal. Although  several waste products are being investigated as choices  for coarse total, this investigation is intended to propose  a substitute material returning coal washing, also known  as coal washery rejects (CWR), as a unique option for  coarse total inside the solid business.
Keywords: Coal Washery Rejects Bottom Ash; Fine Aggregate; Mechanical Properties